Structure of a territorial brand - Maria A. Belyaeva (Управление культурой)
Understanding how the phenomenon of a territorial brand works is one of the conditions for ensuring the competitiveness of territories. This is where the objectives of this article arise - to study existing ideas about the structure of a territorial brand, give examples of modeling this structure, and propose the author's model of the structure of a territorial brand. The results of theoretical research based on general logical methods (analysis, synthesis, etc.) and the methodology of systemic, activity-based, axiological approaches are presented in the article. There is some limitation of the subject of the study, since the author narrows the meaning of the concept of “territorial brand”, specifying the scale of space to an urban settlement. The author identified four models of the territorial brand structure developed by M. S. Kagan, S. Anholt, K. Dinnie, as well as his own model (M. A. Belyaeva, T. A. Ladygina), outlining the possibilities of using each of them. According to the author's vision, the structure of a territorial (city) brand can be formalized in the form of a conventional circle with several diameters: the “core” of the brand is the idea, values and norms (“spirit of the place”); the next perimeter is knowledge, then technologies and cultural practices, and the outer, most voluminous perimeter is the substantive content of the brand. In the peripheral parts of its structure, the brand flows from the world of ideas into the material dimension, proving the realism of the image and creating conditions for its sensory perception. This model is useful in the process of strategic urban development planning, when many private decisions for several years (or even centuries) are determined by a key idea. The text contains examples that relate theory to practice. The author believes that geobranding, as a process of forming and promoting the image of a place, requires cultural justification, and the presence of well-founded ideas about the structure of a territorial brand serves as a reliable compass on the way to building the image of a particular city, translating the chaos of multidirectional efforts (in politics, economics, tourism, media and other areas) into a controlled direction.